Golden Plantation Berhad: Proposed Acquisition of Plaza Cahaya - Fong, Chee Khuen (1999)
Golden Plantation Berhad (GPB) was incorporated on I October 1968 with its principal activities in those early years involving in the cultivation of sugar cane, processing of cane, refined sugar and its by-product in Dinding, Perak. GPB was officially listed on the Kuala Lumpur Stock Exchange (KLSE) and Stock Exchange of Singapore (SES) on 3 May 1971. However, trading of GPB's shares was suspended when the company ceased operation in 1975 due to continuing operating losses. With the completion of the relevant stages of Reconstruction Scheme, these shares were relisted on 1 November 1989. Subsequently, in compliance with Malaysia Government's policy and KLSE's requirement, GPB's shares were delisted from SES with effective from 1 January 1990. The Reconstruction Scheme in Feb 1989 had successfully restructured and transformed OPB by way of acquisition of income-producing oil palm plantation estates. Following another recent corporate exercise in 1995, GPB had ventured into two major businesses namely property development sector and hotel services sector by acquiring few pieces of landbank in the Klang Valley and the acquisition of Dyman Corporation (M) Sdn Bhd which owned the Century Hotel Kuala Lumpur (CHKL).